A Facile Approach of Fabricating Bifunctional Catalysts for Redox Applications by Uniformly Immobilized Metallic Nanoparticles on NiCr LDH - Mosaed S. Alhumaimess; Obaid F. Aldosari; Almaha N. Alqhobisi; Laila M. Alhaidari; Afnan Altwala; Linah A. Alzarea; Hassan M. A. Hassan (Nanomaterials, 2023)
This study discloses the development of NiCr LDH, Ag@NiCr LDH, and Pd@NiCr LDH bifunction catalysts using a hydrothermal coprecipitation method followed by sol immobilization of metallic nanoparticles. The structures and morphologies of the synthesized nanocomposites were analyzed using FTIR, XRD, XPS, BET, FESEM-EDX, and HRTEM. The catalytic effectiveness of the samples was evaluated by tracking the progression of NaBH4-mediated nitrobenzene (NB) reduction to aniline and CO oxidation using UV-visible spectrophotometry and an infrared gas analyzer, respectively. Pd@NiCr LDH displayed much higher performance for both reactions than the bare NiCr LDH. The catalyst Pd@NiCr LDH showed robust catalytic activity in both the oxidation of carbon monoxide (T50% (136.1 °C) and T100% (200.2 °C)) and NaBH4-mediated nitrobenzene reduction (98.7% conversion and 0.365 min−1 rate constant). The results disclose that the Ni2+@ Cr3+/Cr6+ @Pd° ion pairs inside the LDH act as a charge transfer center and hence significantly enhance the catalytic performance. As a result, this research offers the novel NiCr LDH catalyst as a bifunctional catalyst for air depollution control and the organic transformation process.